Cevaplar

2012-10-14T12:33:38+03:00

x / ( x + 1 ) = 1 / 3 + ( x + 2 ) / 4x
4x^2 / ( x + 1 ) = 4x / 3 + ( x + 2 )
4x^2 = 4x ( x + 1 ) / 3 + ( x + 2 ) ( x + 1 )
12x^2 = 4x ( x + 1 ) + 3 ( x + 2 ) ( x + 1 )
12x^2 = 4x^2 + 4x + 3x^2 + 9x + 6
12x^2 = 7x^2 + 13x + 6
5x^2 - 13x - 6 = 0
x1 = ( 13 + ( 169 + 120 )^0,5 ) / 10
x1 = ( 13 + 17 ) / 10 = 3
x2 = ( 13 - 17 ) / 10 = - 2 / 5

2x^3 + 4x^2 - 5x - 3 = ( 2x^2 - 5 ) ( x + 2 ) + 7

0
2012-10-14T12:54:29+03:00

x / ( x + 1 ) = 1 / 3 + ( x + 2 ) / 4x
 4x^2 / ( x + 1 ) = 4x / 3 + ( x + 2 )
4x^2 = 4x ( x + 1 ) / 3 + ( x + 2 ) ( x + 1 ) 
     12x^2 = 4x ( x + 1 ) + 3 ( x + 2 ) ( x + 1 ) 
    12x^2 = 4x^2 + 4x + 3x^2 + 9x + 6
 12x^2 = 7x^2 + 13x + 6
  5x^2 - 13x - 6 = 0
x1 = ( 13 + ( 169 + 120 )^0,5 ) / 10
x1 = ( 13 + 17 ) / 10 = 3
x2 = ( 13 - 17 ) / 10 = - 2 / 5

   2x^3 + 4x^2 - 5x - 3 = ( 2x^2 - 5 ) ( x + 2 ) + 7

0